Biological cycling of volatile organic carbon by phytoplankton and bacterioplankton. (31st May 2017) - Halsey, Kimberly H.; Giovannoni, Stephen J.; Graus, Martin; Zhao, Yanlin; Landry, Zachary; Thrash, J. Cameron; Vergin, Kevin L.; de Gouw, Joost
Abstract: Acetaldehyde, methanol, acetone, and isoprene are important reactive volatile organic compounds (VOCs) in the oceans that partition to the atmosphere in significant amounts. Reports of potentially high rates of VOC turnover in the North Atlantic suggested that both biotic and abiotic processes are involved. The biological basis for VOC cycling by ocean plankton is unknown, but is potentially important because of VOC contributions to carbon cycle budgets and atmospheric chemistry. We designed dynamic stripping chambers that coupled to a proton transfer reaction mass spectrometer to measure VOC production and consumption by cultured phytoplankton and bacterioplankton. The diatom, Thalassiosira pseudonana, produced acetaldehyde in a light‐dependent manner. Acetaldehyde was oxidized by the chemoheterotrophic bacterium, Pelagibacter, at rates that suggest that most acetaldehyde is recycled in the ocean before escaping to the atmosphere. These results show that field observations of acetaldehyde turnover reported previously could be explained by biological activity. Rates of production by phytoplankton cultures of methanol, acetone, and isoprene were also measured. These findings support the conclusion that VOCs are a conduit for carbon transfer directly from phytoplankton to bacterioplankton, with the remainder available for escape to the atmosphere.